DESAIN TRAFO DAYA MENGGUNAKAN STUDI MINYAK BIODEGRADABLE UNTUK KEBERLANJUTAN - Indarto, Agus; Bohra, Arunkumar; Wahyudi, Slamet; Dharmanto, Asep (Jurnal Media Elektro, 2024)
To achieve net carbon zero in the electrical transmission and distribution industry, advancements in design, manufacturing, and materials are essential, particularly for power transformers. Traditional mineral oil, used for insulation and cooling, poses environmental challenges due to its non-biodegradability, low fire point, and lack of eco-friendliness. Alternative insulating fluids, both synthetic and natural esters, offer improved fire safety and environmental compatibility. Recent research has enhanced understanding of ester fluids' electrical, thermal, and chemical properties, yet adoption is hindered by limited research, unestablished testing methods, and experience. This study explores the design and manufacturing challenges of power transformers using ester insulating oil compared to those filled with mineral oil, focusing on weight, dimensions, cost, and the impact of smart monitoring systems on performance, longevity, maintenance, and reliability. The study also examines the influence of renewable energy and micro-grids on the design and manufacturing of ester oil-filled transformers. This comparison aims to guide both customers and manufacturers in evaluating the suitability of ester-filled transformers for specific applications, ultimately contributing to more informed decision-making and advancing the industry's sustainability goals.